[tex]\left(x+2\sqrt{3}\right)\left(3-\sqrt{3}\right)=9+\sqrt{3}[/tex]
Dzielę obustronnie przez [tex]3-\sqrt{3}[/tex]
[tex]\frac{\left(x+2\sqrt{3}\right)\left(3-\sqrt{3}\right)}{3-\sqrt{3}}=\frac{9}{3-\sqrt{3}}+\frac{\sqrt{3}}{3-\sqrt{3}}[/tex]
[tex]x+2\sqrt3=\frac{9+\sqrt{3}}{3-\sqrt{3}}[/tex]
[tex]\mathrm{Odejmujemy\:}2\sqrt{3}\mathrm{\:obustronnie}[/tex]
[tex]x+2\sqrt{3}-2\sqrt{3}=\frac{9+\sqrt{3}}{3-\sqrt{3}}-2\sqrt{3}[/tex]
jednocześnie pozbywam się niewymierności z mianownika z prawej strony:
[tex]x=\frac{\left(9+\sqrt{3}\right)\left(3+\sqrt{3}\right)}{\left(3-\sqrt{3}\right)\left(3+\sqrt{3}\right)}-2\sqrt3[/tex]
[tex]x=\frac{30+12\sqrt{3}}{6}-2\sqrt3\\x=\frac{6\left(5+2\sqrt{3}\right)}{6}-2\sqrt3\\x=5+2\sqrt3-2\sqrt3\\\boxed{x=5}[/tex]